Therapeutic Plants: Recent Advances in the Use of Herbs as Alternative Medications - V. Sathibabu Uddandrao, V.; Saravanan, G. (Bentham Science Publishers, 2025)
Therapeutic Plants: Recent Advances in the Use of Herbs as Alternative Medications offers an in-depth exploration of how herbs are reshaping modern healthcare. Bridging traditional knowledge and scientific innovation, the book highlights the therapeutic power of medicinal plants in managing chronic diseases like diabetes, cancer, and cardiovascular disorders. It explores bioactive compounds, Ayurvedic principles, and advanced drug delivery systems, including nanoparticles. Chapters cover disease-specific applications, plant-based drug discovery, and the role of metabolomics and in-silico methods in drug design. The book also features detailed studies on specific herbs like Barleria longiflora, Terminalia chebula, and Lawsonia inermis. Key Features: - Scientific insights into herbal treatments for chronic diseases. - Integration of traditional and modern medicine. - Innovative delivery systems, including nanotechnology. - In-silico drug design and metabolomics applications. - Case studies of medicinal plants and their bioactive compounds.